Die konzeptuelle Metapher ZEIT ALS RAUM im FrameNet-Konstruktikon des Deutschen - Neumair, Phillip Alexander (Linguistik Online, 2026)
Based on the epistemological tenet that time and space are the two fundamental concepts of our thinking, this article presents a frame-semantic approach to the conceptualisation of time as space. It shows that the chosen cognitive linguistic approach is capable of capturing the stable anchoring of the two domains in the conceptual system: Following a network model of knowledge, the time as space metaphor is established as a metaphor family in the “German FrameNet-Constructicon”. Its family members are described corpus-based and in detail. Here, the intertwining of different conceptual metaphors also proves to be significant.